175k views
0 votes
C(n) = -6 \left(-\dfrac{1}{3}\right)^{n - 1}c(n)=−6(− 3 1 ​ ) n−1 c, left parenthesis, n, right parenthesis, equals, minus, 6, left parenthesis, minus, start fraction, 1, divided by, 3, end fraction, right parenthesis, start superscript, n, minus, 1, end superscript What is the 2^\text{nd}2 nd 2, start superscript, start text, n, d, end text, end superscript term in the sequence?

User Hidarikani
by
4.5k points

1 Answer

2 votes

Answer: The second term of the sequence is 2

Explanation:

Given the function c(n) = -6(-1/3)^n-1

To get the second term of the sequence, we will substitute n =2 into the given function to have;

c(2) = -6(-1/3)^2-1

c(2) = -6(-1/3)^2-1

c(2) = -6(-1/3)^1

C(2) = -6(-1/3)

Since -×- a= +

C(2) = +6/3

C(2) = 2

Therefore the second term of the sequence is 2

User Thomas Lumley
by
5.2k points